Prospects for the development of Sharia financing contract on KPR Syariah iB Hebat at BPRS Dana Amanah Surakarta - Sup, Devid Frastiawan Amir; Firdaus, Muhammad Irkham; Bilhaq, Aqil Mutashim (Universitas Islam Indonesia, 2024)
IntroductionThe KPR Syariah iB Hebat product at BPRS Dana Amanah Surakarta currently uses murabahah, istishna', and MMQ contracts. However, from the perspective of regulations and fatwa, the KPR Syariah can also be developed using the salam contract, IMBT contract, IMFD contract, and MMBT contract.ObjectivesThis research aims to analyze the prospects for developing Sharia financing contracts on KPR Syariah iB Hebat at BPRS Dana Amanah Surakarta.MethodThis research uses a qualitative, descriptive, field research approach. Primary data are in the form of literature review results and field data findings, while secondary data are in the form of other data sources that support primary data, such as books, journal articles, and websites. Data were obtained using observation, interview, and documentation methods and then analyzed using the inductive method.ResultsAccording to the results obtained, BPRS Dana Amanah Surakarta should consider six risks: credit risk, operational risk, compliance risk, liquidity risk, reputation risk, and strategic risk.ImplicationsBased on the analysis of the characteristics of the KPR Syariah iB Hebat at BPRS Dana Amanah Surakarta, the contract prospects to be developed are the salam contract, IMBT contract, and IMFD contract.Originality/NoveltyThis research made an important contribution in the form of contract prospects to be developed in the context of BPRS in Indonesia, which has similarities with KPR Syariah iB Hebat at BPRS Dana Amanah Surakarta.